Modern Strategy of Educational Planning - Awokoya, S. Oluwole (Obafemi Awolowo University Press, 2013)
I have chosen Modern Strategy of Educational Planning as the theme of this lecture because of its relevance to the rigorous battle for survival which all developing countries are facing in this scientific and technological age.